2018
DOI: 10.1016/j.tics.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Electrophysiology of the Human Default Network

Abstract: The human default network (DN) plays a critical role in internally directed cognition, behavior, and neuropsychiatric disease. Despite much progress with functional neuroimaging, persistent questions still linger concerning the electrophysiological underpinnings, fast temporal dynamics, and causal importance of the DN. Here, we review how direct intracranial recording and stimulation of the DN provides a unique combination of high spatiotemporal resolution and causal information that speaks directly to many of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
70
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 165 publications
(250 reference statements)
6
70
1
Order By: Relevance
“…More substantively, our lack of significant correlation for scene‐task related PCu/PCC BOLD with local GABA+ and Glx could be consistent with accounts that different populations of neurons within posterior DMN have somewhat distinct functions. Single unit recording studies have recently revealed that neural populations in PCu/PCC associated with “default mode” activity (i.e., showing task‐negative responses) may be distinct from those involved in active (e.g., mnemonic or scene‐construction) processing (Daitch & Parvizi, ; Fox et al, ). In addition, patterns of DMN network connectivity are somewhat different during rest versus autobiographical memory and future thinking (Bellana, Liu, Diamond, Grady, & Moscovitch, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More substantively, our lack of significant correlation for scene‐task related PCu/PCC BOLD with local GABA+ and Glx could be consistent with accounts that different populations of neurons within posterior DMN have somewhat distinct functions. Single unit recording studies have recently revealed that neural populations in PCu/PCC associated with “default mode” activity (i.e., showing task‐negative responses) may be distinct from those involved in active (e.g., mnemonic or scene‐construction) processing (Daitch & Parvizi, ; Fox et al, ). In addition, patterns of DMN network connectivity are somewhat different during rest versus autobiographical memory and future thinking (Bellana, Liu, Diamond, Grady, & Moscovitch, ).…”
Section: Discussionmentioning
confidence: 99%
“…Much of our knowledge of the role of PCu/PCC in scene-related cognition is based on measurements tied to neuronal activity, including blood-oxygenation-level dependent (BOLD) functional magnetic resonance imaging (fMRI) in humans (Bzdok et al, 2015;Spreng, Mar, & Kim, 2009) and single unit recording studies in both humans (Fox, Foster, Kucyi, Daitch, & Parvizi, 2018) and nonhuman primates (Dean, 2006;Sato, Sakata, Tanaka, & Taira, 2010). Further evidence comes from neuropsychological investigations of scene-based processing following brain lesions (Futamura et al, 2018;Suzuki, Yamadori, Hayakawa, & Fujii, 1998), including Alzheimer disease-linked neurodegeneration (Chan et al, 2016;Irish et al, 2015).…”
mentioning
confidence: 99%
“…Furthermore, regarding default mode, intracranial electrophysiology studies demonstrate different patterns of activity across multiple regions of the default mode over time (for review please read (Fox et al, 2018)). The concept of spatial dynamics and variations in regions’ associations over time was also confirmed via the amplitude of BOLD signal.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there has been a dramatic increase in the number of functional neuroimaging and electrophysiological studies aiming to elucidate the neural correlates of self‐generated cognition. A general picture of the brain networks involved in self‐generated thought is gradually emerging, and initial steps have been taken to correlate the specific sensory modality and emotional valence of self‐generated mental content with specific patterns of brain activity …”
Section: Introductionmentioning
confidence: 99%